Labor of love: The formalization of care in transgender kinship organizations. (November 2021) - Greene, Joss
While prior research shows how community-based organizations (CBO's) create new social ties and solidarities, we know less about CBO's that formalize preexisting relationships of care. Analyzing transgender nonprofits as a strategic case, this article develops the concept of kinship organizations: organizations that incorporate norms, networks, and resources from kinship systems into a formal organization that provides regular social services. Drawing on 7 months of ethnography and 36 formal interviews with staff and clients, I explore how transgender kinship organizations function, develop, and impact broader transgender community. Kinship organizations are highly responsive to crisis, are able to leverage personal and organizational resources, and are therefore capable of providing personalized rapid-response care to very precarious transgender people. On the other hand, subsuming kinship within a nonprofit transforms relationships of mutual care into unidirectional service relationships and relationships of chosen family into work-based hierarchies. This account of kinship organizations contributes to the theory on organizational development and provides new conceptual tools for analyzing boundaries between organizations and communities.